2022
DOI: 10.1186/s12860-022-00423-8
|View full text |Cite
|
Sign up to set email alerts
|

OSGIN2 regulates osteogenesis of jawbone BMSCs in osteoporotic rats

Abstract: Background Augmentation of oxidative stress after estrogen deficiency leading to functional deficiency of jawbone bone marrow mesenchymal stem cells (BMSCs) causes jawbone loss in osteoporosis. OSGIN2, an oxidative stress induced factor, has been found to be associated with skeletal diseases. This study aims to investigate the function of OSGIN2 in jawbone BMSCs of osteoporotic rats. Jawbone BMSCs were used. Results Oxidative stress was increased i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…( 2) Oxidative stress: It has been reported that oxidative stress is a key trigger of osteoporosis. OSGIN2, an inducer of oxidative stress, prevented osteogenic differentiation of BMSCs by inhibiting RORa expression (24,25). ( 3) DNA methylation: Histone methylation has been recognized as an important modulator in the osteogenic differentiation of MSCs (26).…”
Section: Rora In Osteoporosismentioning
confidence: 99%
“…( 2) Oxidative stress: It has been reported that oxidative stress is a key trigger of osteoporosis. OSGIN2, an inducer of oxidative stress, prevented osteogenic differentiation of BMSCs by inhibiting RORa expression (24,25). ( 3) DNA methylation: Histone methylation has been recognized as an important modulator in the osteogenic differentiation of MSCs (26).…”
Section: Rora In Osteoporosismentioning
confidence: 99%